2018
DOI: 10.4018/978-1-5225-2829-6.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Automated Classification of Focal and Non-Focal EEG Signals Based on Bivariate Empirical Mode Decomposition

Abstract: The chapter presents a new approach of computer aided diagnosis of focal electroencephalogram (EEG) signals by applying bivariate empirical mode decomposition (BEMD). Firstly, the focal and non-focal EEG signals are decomposed using the BEMD, which results in intrinsic mode functions (IMFs) corresponding to each signal. Secondly, bivariate bandwidths namely, amplitude bandwidth, precession bandwidth, and deformation bandwidth are computed for each obtained IMF. Interquartile range (IQR) values of bivariate ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The comparison with some state-ofthe-art methods has been presented in Table 6. The classification ACC has been achieved with 99%, which is superior to the considered methods in [5,7,25,26,30] shown in the table using the same Bern-Barcelona dataset for identifying focal and NF EEG signals. From the overall observation, it is concluded that the presented approach in this study is suitable and promising and can be treated as a supporting system for EEG signal classification.…”
Section: Classification Results and Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The comparison with some state-ofthe-art methods has been presented in Table 6. The classification ACC has been achieved with 99%, which is superior to the considered methods in [5,7,25,26,30] shown in the table using the same Bern-Barcelona dataset for identifying focal and NF EEG signals. From the overall observation, it is concluded that the presented approach in this study is suitable and promising and can be treated as a supporting system for EEG signal classification.…”
Section: Classification Results and Discussionmentioning
confidence: 90%
“…proposed approach 100 using Bern-Barcelona dataset (focal versus NF EEG signal classification) focal versus NF Sharma et al [25] entropy measures form 10 IMFs + LSSVM 87.01 Sharma et al [26] bivariate EMD + amplitude bandwidth, precession bandwidth, and deformation bandwidth features 89.5…”
Section: Conclusion and Future Scopementioning
confidence: 99%
See 2 more Smart Citations
“…In recent times, empirical mode decomposition (EMD) has shown potential as a very promising decomposition technique to analyse EEG signals [11]. It has been used for the classification of epileptic EEG signals [20,19] and motor imagery BCI classification problems [5]. However, the single channel EMD method has some potential issues such as mode-mixing and frequency localisation problems.…”
Section: Introductionmentioning
confidence: 99%